Human leptospirosis in Portugal - Vieira, M L (2021)
Leptospirosis, an under-recognized public health problem, needs to be confirmed through specific laboratory diagnosis. We describe herein a series of 4618 symptomatic patients for whom a microagglutination test (MAT) serology was available, representing a unique picture of human leptospirosis in central mainland Portugal and the Azores islands of São Miguel and Terceira, over eighteen- and twelve-year periods, respectively. The distribution of the 1024 (22%) cases identified was an average 57 cases per year, with higher frequency in males (67%). These represent the majority of leptospirosis notifications in Portugal, with a higher annual incidence rate in the islands, compared to the central mainland (11.1 and 1.7/100,000 population, respectively). Middle-aged adults (25-54 years) were most frequently infected (45%). Cases occurred mainly in December and January. Serovars from nine presumptive serogroups caused infection, with a predominance of Icterohaemorrhagiae, Pomona, and Ballum, accounting for 66% of cases. Seropositivity was associated with both anicteric and icteric leptospirosis. Several risk factors and a higher transmission risk in certain areas were emphasized. Leptospirosis was confirmed as a steadily increasing public health problem; good surveillance, communication, and laboratory support are thus necessary to reduce the impact of leptospirosis in areas at risk.